Teachers’ Attitude to the Development of Socially Acceptable Behavior in Children (a Case Study of Radviliškis X Preschool Education Institution) - Smilgienė, Jurgita; Jankutė, Kristina (Jaunųjų mokslininkų darbai, 2019)
The lithuanian public has been undergoing transformations, and our personal values are being influenced by the surrounding environment. Nowadays, human behavior has been gradually worsening and it is especially evident in children and adolescents. Teenagers are growing up less independent, show little respect for others and their nation, talk rudely, they more often reject social norms, thus all that shows that the behavior of our young generation has become less socially acceptable. The earlier children are familiarized with core cultural / social values and develop them, it is more likely that we will achieve better results developing socially acceptable behavior of our society. Thus, both, the family and a preschool education institution, are responsible for developing socially acceptable behavior in children, teaching social and life skills, politeness, respect, honesty, friendliness, etc. The aim of this research was to identify preschool education institution teachers’ attitude to the development of socially acceptable behavior in preschool children. We carried out this research in a Radviliškis preschool education institution, seeking to find out the significance of the development of socially acceptable behavior in a preschool education institution and teachers’ attitude to it. A qualitative research method was chosen. A questionnaire was prepared and filled in by the teachers of this preschool education institution. The collected data were analyzed using content analysis. The research results showed that socially acceptable behavior is a broad concept, it includes conduct, hygiene practices, environmental, national awareness. According to the respondents, the responsibility for the development of socially acceptable behavior lies with the family. Education institutions were identified as institutions contributing to the development of socially acceptable behavior in children.